(untitled) (INTERNATIONAL SEMINAR, 2025)
This research aimed to determine whether students’ anxiety levels have the influence on their speaking ability in EFL speaking class. The population of this research consisted of third semester students from the English Study Program of FKIP UIR, class A and B, with 30 students randomly selected as the sample. The research employed a descriptive quantitative design using a questionnaire and a presentation test as instruments. The questionnaire used was the Foreign Language Classroom Anxiety Scale (FLCAS) developed by Horwitz et al. (1986), while the presentation test was assessed using a presentation rubric evaluated by two raters to ensure the reliability of the test. The results indicated a significant negative influence on students’ anxiety levels and their speaking test scores from rater 1, and rater 2. The strength of this influence was categorized as moderate, and the direction of the influence was negative, meaning that higher anxiety level were associated with lower speaking test. Furthermore, the findings revealed that most students were categorized as “Mildly Anxious” in terms of anxiety level and “Basic” in their presentation. It can be concluded that anxiety can affect students’ speaking ability, especially when making presentations in front of the class. Several factors such as fear of making mistakes, being seen by many people, or being interrupted by lecturers can increase students’ anxiety level.